Checkpoint TIPE2 Limits the Helper Functions of NK Cells in Supporting Antitumor CD8+ T Cells - Jiacheng Bi; Xiaomeng Jin; Chaoyue Zheng; Chen Huang; Chao Zhong; Xiaohu Zheng; Zhigang Tian; Haoyu Sun (Advanced Science, 2023)
Abstract Natural killer (NK) cells not only are innate effector lymphocytes that directly participate in tumor surveillance but are also essential helpers in the antitumor CD8+ T‐cell response. However, the molecular mechanisms and potential checkpoints regulating NK cell helper functions remain elusive. Here, it is shown that the T‐bet/Eomes‐IFN‐γ axis in NK cells is essential for CD8+ T cell‐dependent tumor control, whereas T‐bet‐dependent NK cell effector functions are required for an optimal response to anti‐PD‐L1 immunotherapy. Importantly, NK cell‐expressed TIPE2 (tumor necrosis factor‐alpha‐induced protein‐8 like‐2) represents a checkpoint molecule for NK cell helper function, since Tipe2 deletion in NK cells not only enhances NK‐intrinsic antitumor activity but also indirectly improves the antitumor CD8+ T cell response by promoting T‐bet/Eomes‐dependent NK cell effector functions. These studies thus reveal TIPE2 as a checkpoint for NK cell helper function, whose targeting might boost the antitumor T cell response in addition to T cell‐based immunotherapy.